The English-Chinese pocket PINYIN dictionary Ying Han pin yin xiu zhen ci dian - Wu, Zhaoyi (New World Press, 1988)
This dictionary "has been specially prepared for English speakers who study Chinese." In each entry the Chinese characters are followed by pinyin, the Chinese phonetic transcription.